Emerging Trends on the Correlation Between Neurotransmitters and Tumor Progression in the Last 20 Years: A Bibliometric Analysis via CiteSpace - Shi, Yumiao; Luo, Jiamei; Wang, Xiaoqiang; Zhang, Yiqi; Zhu, Hui; Su, Diansan; Yu, Weifeng; Tian, Jie (Frontiers in Oncology, 2022)
Background: Bibliometric analysis is used to gain a systematic understanding of developments in the correlation between neurotransmitters and tumor progression in research hotspots over the past 20 years. Methods: Relevant publications from the Web of Science Core Collection (WoSCC) were downloaded on August 1, 2021. Acquired data were then analyzed using the Online Analysis Platform of Literature Metrology (http://biblimetric.com) and the CiteSpace software to analyze and predict trends and hot spots in this field. Results: A total of 1310 publications on neurotransmitters and tumor progression were identified, and 1285 qualified records were included in the final analysis. The country leading the research was the United States of America. The University of Buenos Aires featured the highest number of publications among all institutions. Co-citation cluster labels revealed the characteristics of 10 main clusters: beta-adrenergic receptors (β-AR), glutamate, neurotransmitters, serotonin, drd2, histamine, glycine, interleukin-2, neurokinin receptor-1, and nicotinic acetylcholine receptors (AchRs). Keywords and references burst detection indicated that apart from β-AR, dopamine receptor and cancer types like gastric cancer and glioblastoma are the newly emerging research hotspots. Conclusions: This study analyzed 1285 publications and 39677 references covering the topic of neurotransmitters and tumor progression and showed that while β-AR has always been a hot topic in this field, dopamine receptor is an emerging target for this research field, and gastric cancer and glioblastoma are the top two tumors that have garnered increasing attention and have become the focal point of recent studies.